IRAK1 and IRAK4 as emerging therapeutic targets in hematologic malignancies. Issue 1 (January 2022) - Bennett, Joshua; Starczynowski, Daniel T.
Abstract : Purpose of review: Cell intrinsic and extrinsic perturbations to inflammatory signaling pathways are a hallmark of development and progression of hematologic malignancies. The interleukin 1 receptor-associated kinases (IRAKs) are a family of related signaling intermediates (IRAK1, IRAK2, IRAK3, IRAK4) that operate at the nexus of multiple inflammatory pathways implicated in the hematologic malignancies. In this review, we explicate the oncogenic role of these kinases and review recent therapeutic advances in the dawning era of IRAK-targeted therapy. Recent findings: Emerging evidence places IRAK signaling at the confluence of adaptive resistance and oncogenesis in the hematologic malignancies and solid tissue tumors. Preclinical investigations nominate the IRAK kinases as targetable molecular dependencies in diverse cancers. Summary: IRAK-targeted therapies that have matriculated to early phase trials are yielding promising preliminary results. However, studies of IRAK kinase signaling continue to defy conventional signaling models and raise questions as to the design of optimal treatment strategies. Efforts to refine IRAK signaling mechanisms in the malignant context will inspire deliberate IRAK-targeted drug development and informed combination therapy.